2019
DOI: 10.3389/fimmu.2019.00974
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Mediators From Timothy Grass Pollen Contribute to the Effector Phase of Allergy and Prime Dendritic Cells for Glycolipid Presentation

Abstract: Plant pollen are an important source of antigens that evoke allergic responses. Protein antigens have been the focus of studies aiming to elucidate the mechanisms responsible for allergic reactions to pollen. However, proteins are not the sole active agent present in pollen. It is known that pollen grains contain lipids essential for its reproduction and bioactive lipid mediators. These small molecular compounds are co-delivered with the allergens and hence have the potential to modulate the immune response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…For instance, Minghetti et al showed the ability of the phytoprostane B 1 -PhytoP, through novel mechanisms involving PPAR-γ, to specifically affect immature brain cells, such as neuroblasts and oligodendrocyte progenitors, thereby conferring neuroprotection against oxidant injury and promoting myelination [58]. Duda et al showed the role, also as lipid mediator, of some phytoprostanes in the immediate effector phase of allergic inflammation [38]. More recently, the work of Lee et al put forward the hypothesis of the neuroprotective effect of 4-F 4t -NeuroP in cellular and animal models [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Minghetti et al showed the ability of the phytoprostane B 1 -PhytoP, through novel mechanisms involving PPAR-γ, to specifically affect immature brain cells, such as neuroblasts and oligodendrocyte progenitors, thereby conferring neuroprotection against oxidant injury and promoting myelination [58]. Duda et al showed the role, also as lipid mediator, of some phytoprostanes in the immediate effector phase of allergic inflammation [38]. More recently, the work of Lee et al put forward the hypothesis of the neuroprotective effect of 4-F 4t -NeuroP in cellular and animal models [59].…”
Section: Discussionmentioning
confidence: 99%
“…Such a protocol has proven to be efficient for similar analyses in the past [34,35]. Isoprostanoids were subsequently separated, identified and quantified using a micro-LC-MS/MS method validated by previous studies [36][37][38]. Identification relied on retention times observed during spiked experiments, determination of molecular masses and the analysis of specific MS/MS transitions.…”
Section: Analysis Of Extraction Yield and Matrix Effectmentioning
confidence: 99%
“…Whether sensitization to pollen-derived allergens occurs at the oral mucosa, the olfactory or corneal epithelium is still a matter of debate; the skin has also been proposed as a sensitization route for allergenic pollen [44][45][46]. Upon encounter, the pollen hydrates and releases a hydrophilic cocktail consisting of allergenic and non-allergenic proteins and various other bioactive molecules, including lipid mediators, inducing an inflammatory milieu favouring Th2 polarization [47][48][49][50][51].…”
Section: The Activation Of the Innate Immune Systemmentioning
confidence: 99%
“…Cypress pollen-derived phospholipids were shown to be presented by MHC-related molecules on DCs to T cells via CD1, an interaction causing T cell proliferation and secretion of IFN-γ and IL-4 in cypress-sensitized individuals, but not in healthy controls [ 122 , 127 , 128 ]. Contribution of invariant natural killer T (iNKT) cells in mediating the effects of pollen lipids was also described for olive and birch pollen in humans and in murine in vitro models, respectively [ 50 , 127 ].…”
Section: The Concept Of the Pollen Matrix In Allergic Sensitizationmentioning
confidence: 99%
“…Because of their structural analogy to mammalian oxylipins derived from arachidonic acid, such as isoprostanes and prostaglandins, on which have been demonstrated a number of biological actions, PhytoP have been suggested to be capable of mimicking the biological activity of those compounds in mammals after dietary ingestion (Durand et al, 2011; Galano et al, 2017). In fact, various bioactivities, for example, neuroprotection and anti‐inflammatory activities, have been reported for PhytoP in humans (Gonzalez Roldan et al, 2019; Martínez Sánchez et al, 2020; Minghetti et al, 2014). In contrast, the function of PhytoP and PhytoF in planta is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%